Narrating Deliverance: The Literary Double in the Writing of Chitra Banerjee Divakaruni, Jhumpa Lahiri, and Bharati Mukherjee - Arjopalo, Nana (fi=Turun yliopisto|en=University of Turku|, 2023)
This dissertation studies the literary double in contemporary fiction by three Bengali American writers: Chitra Banerjee Divakaruni, Jhumpa Lahiri, and Bharati Mukherjee. The main focus is on examining what is expressed by the double, and in finding reasons for its recurrence in this fictional genre that mainly explores the migrant experience in the United States. The dominant idea of an individualized selfhood is largely a Western construction and has been increasingly contested by diffused and decentered subjectivities. The literary double blurs boundaries between individual subjectivity and the community, expressing more than a singular ‘I’ could, and thus forges new forms of selfhood. These non-unitary subjectivities often emerge in the writing of nondominant or marginalized subjects such as women and ethnic minorities. In literary history, the double has often been reduced to an evil foil to the protagonist, but this dissertation broadens the concept of the double from a mere trope to a literary device reflective of its era, performing cultural work. The texts studied in this dissertation are Sister of My Heart (1999) and The Vine of Desire (2002) by Divakaruni, “Hema and Kaushik” (a novella in the short story collection Unaccustomed Earth, 2008) and The Lowland (2013) by Lahiri, and Desirable Daughters (2002), The Tree Bride (2004), and Miss New India (2011) by Mukherjee. These works were published at the turn of the new millennium, paralleled by a theoretical reorientation from a socio-realist critique of postcolonial and world literatures toward a more aesthetically focused approach. The dissertation argues that in the primary texts listed above, the literary double challenges the concept of individual subjectivity with a dual or non-unitary subjectivity, informed by the postcolonial context. Second, its frequent occurrence is connected to the bi-cultural identity of the Bengali American writers and their characters. Finally, it gives voice to that which has been silenced, functioning as a narrative vehicle for deliverance from the past – from individual, familial, or colonial trauma.

-- Väitöskirja käsittelee kaunokirjallista kaksoisolentoa Chitra Banerjee Divakarunin, Jhumpa Lahirin ja Bharati Mukherjeen 2000-luvun teoksissa. Tutkimuksen päätarkoitus on selvittää, mitä kaksoisolennolla ilmaistaan kyseisissä teoksissa, sekä löytää syitä sen esiintyvyydelle kaunokirjallisuudessa, jossa pääsääntöisesti kuvataan bengalilais-amerikkalaisten elämää Yhdysvalloissa. Vallalla oleva käsitys yksilösubjektiviteetista on ennen kaikkea länsimainen konstruktio, jota jaettu tai jakautunut subjektiviteetti yhä yleisemmin haastaa. Kaunokirjallinen kaksoisolento hämärtää rajoja yksilön ja yhteisön välillä ilmaisten enemmän kuin mihin erillinen ”minä” pystyy, luoden minuuden uusia muotoja. Jaetun subjektiviteetin kuvauksia esiintyy tyypillisesti valta-asemien ulkopuolisten ja marginalisoitujen yksilöiden kuten naisten tai etniseen vähemmistöön kuuluvien teksteissä. Kirjallisuushistoriassa kaksoisolento on usein typistetty yksiulotteiseksi päähenkilön piilotetun pahuuden ruumiillistumaksi. Väitöskirja laajentaa näkemyksen kaksoisolennosta kaunokirjallisesta troopista kohti kulttuurista konstruktiota, joka heijastaa aikansa ilmiöitä ja arvoja. Väitöskirjan ensisijainen tutkimusaineisto koostuu seuraavista teoksista: Divakarunin Sister of My Heart (1999) ja The Vine of Desire (2002), Lahirin “Hema and Kaushik”, episodimainen pienoisromaani novellikokelmassa Unaccustomed Earth (2008; suomeksi Tuore maa) ja The Lowland (2013; suomeksi Tulvaniitty), sekä Mukherjeen Desirable Daughters (2002), The Tree Bride (2004) ja Miss New India (2011). Teokset ovat ilmestyneet vuosituhannen vaihteessa, jolloin jälkikolo-niaalisessa kaunokirjallisuudentutkimuksessa siirryttiin sosiorealistisesta tulkinnasta kohti teosten muotoa ja estetiikkaa huomioivampaa suuntaa. Yllä mainituissa teoksissa kaunokirjallinen kaksoisolento haastaa yksilösubjektiviteetin jaetun subjektiviteetin käsitteellä, jonka syntyprosessissa jälkikoloniaalisella kontekstilla on merkittävä rooli. Kaksoisolennon tiheä esiintyvyys tässä kirjallisuudenlajissa myös heijastaa bengalilais-yhdysvaltalaisten kirjailijoiden ja heidän henkilöhahmojensa kaksikulttuurista identiteettiä. Kaksoisolento kerronnallisena välineenä antaa äänen vaiennetulle, vapauttaen ja eheyttäen yksilön henkilökohtaisesta, yhteisöllisestä tai koloniaalisesta traumasta.